2020
DOI: 10.1177/0954411920923541
|View full text |Cite
|
Sign up to set email alerts
|

A case study on interface pressure pattern of two garment orthoses on a child with cerebral palsy

Abstract: Many studies have shown that medical compression products produce different levels of interface pressure during the usage of the products. However, limited studies have explored the pattern of interface pressure exerted by orthotic garments. This case study aimed to investigate the pattern of interface pressure exerted by two types of orthotic garments on a child with cerebral palsy. A 13-year-old child diagnosed with ataxic spastic diplegia cerebral palsy has difficulty to perform sit-to-stand motion even wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
0
0
Order By: Relevance
“…Several studies have shown that orthotic garments can provide the structural correction that can help improve posture and functional abilities in children with CP (Flanagan et al, 2009). Orthotic garments produce interface pressure that holds the patient's limbs while in a static or dynamic posture (Shaari et al, 2020). The garments reduce fluctuations in tone and contracture of the muscles to improve postural alignment and stability (Bahramizadeh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that orthotic garments can provide the structural correction that can help improve posture and functional abilities in children with CP (Flanagan et al, 2009). Orthotic garments produce interface pressure that holds the patient's limbs while in a static or dynamic posture (Shaari et al, 2020). The garments reduce fluctuations in tone and contracture of the muscles to improve postural alignment and stability (Bahramizadeh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%